The Implementation of CTL Method in teaching English to the students of MAN 1 Enrekang (Universitas Negeri Semarang, 2021)
This research shows the implementation of contextual teaching and learning conducted by the English teachers of MAN 1 Enrekang in teaching English. MAN 1 Enrekang is senior high school that is located in Enrekang regency, Sulawesi Selatan, as one of the schools where most of the teachers there implement CTL method in teaching, include teaching English. However, sometimes the students still find it difficult to understand the material being taught, especially English. This research employed descriptive qualitative method, in which the data collected and analyzed qualitatively by giving description about the phenomena or facts have been found in the field. The subjects of the research were the English teachers of MAN 1 Enrekang. They are English teachers who have implemented CTL in teaching English. Based on the result, it can be concluded that the implementation of CTL method in teaching English to the students of MAN 1 Enrekang was not totally or fully conducted. There are seven elements should be applied in teaching and learning for implementing CTL. They are constructivism, inquiry, modeling, reflection, learning community, questioning, and authentic assessment. Eventhough the teachers understood and admitted implementing CTL in teaching English, the result of the observation shows that the English teachers applied only five elements of CTL in the classroom, while there were two elements of CTL those have not been applied because of the limited time in teaching and learning process, they are constructivism and inquiry. The element of CTL that was applied frequently is questioning